Met-tRNA(f)(Met) Binding to 40S Ribosomal Subunits: A Site for the Regulation of Initiation of Protein Synthesis by Hemin - Clemens, Michael J. (1974)
On incubation of reticulocyte lysates at 30° in the absence of added hemin, protein synthesis declines sharply within 4-6 min, due to the action of a translational inhibitor. Partially purified preparations of this inhibitor, in concentrations that inhibit protein synthesis in the lysate, cause reduced binding of Met-tRNA(f)(Met) to derived 40S ribosomal subunits in a ribosomal-salt-wash-dependent assay system. Neither the association of salt wash proteins with the subunits nor the level of Met-tRNA(f)(Met) bound in preformed 40S complexes is reduced by the inhibitor. No Met-tRNA(f)(Met) deacylase activity could be detected in the inhibitor preparation. Protein synthesis in reticulocyte lysates lacking added hemin or containing exogenous inhibitor is maintained by addition of small amounts of an initiation preparation factor, “F-MP,” which may be involved in the binding of Met-tRNA(f)(Met) to 40S subunits. This binding constitutes a site for control of protein synthesis by hemin in reticulocytes.